Immune reconstitution inflammatory syndrome, human herpesvirus 8 viremia, and HIV-associated multicentric Castleman disease. (July 2016) - Siegel, Marc O.; Ghafouri, Sanaz; Ajmera, Ravi; Simon, Gary L.
Summary: Kaposi's sarcoma and multicentric Castleman Disease are HIV-related disease processes that are associated with human herpesvirus 8 (HHV-8) infection. The development of multicentric Castleman disease can often be a manifestation of the immune reconstitution inflammatory syndrome phenomenon and is associated with markedly elevated levels of HHV-8 viremia, as illustrated by this case.